Effect of Inorganic and Organic Nitrogen Sources and Biofertilizer on Murcott Mandarin Fruit Quality - Ahmed M. Fikry; Khadija S. Radhi; Mohammed A. S. Abourehab; Talaat A. M. Abou Sayed-Ahmed; Mohamed M. Ibrahim; Farid S. Mohsen; Nour A. Abdou; Ahmad A. Omar; Ibrahim Eid Elesawi; Mohamed T. El-Saadony (Life, 2022)
Mandarin ‘Murcott’ (Citrus reticulata Blanco) trees aged five years that were grafted onto lemon ‘Volkamer’ (Citrus volkameriana) rootstock and grown in sandy soil under a drip irrigation system were used in this study during the growing seasons of 2018 and 2019. Ten different fertilization treatments combining inorganic, organic, and biofertilization in a completely randomized block were performed. The results revealed that fertilizing ‘Murcott’ mandarin trees with 75% of the recommended dose (RD) of nitrogen as inorganic nitrogen (33.5% N) in the form of NH4NO3 + 25% of RD as organic nitrogen in the form of chicken manure (3% N) per tree per year without or with a biofertilizer (Effective Microorganisms, EM1) at 150 mL/tree increased the weight, size, pulp, and peels of mandarin fruit, as well as the fruit juice volume, juice volume/fruit, and vitamin C, but reduced the total acidity in both seasons. However, fertilizing ‘Murcott’ mandarin trees with 100% of RD as inorganic nitrogen increased the pulp/fruit ratio, and fertilizing with 25% of RD as inorganic nitrogen + 75% of RD as organic nitrogen + biofertilizer EM1 increased the peel/fruit ratio, peel thickness, and fruit firmness. Fertilizing ‘Murcott’ mandarin trees with 100% organic nitrogen + biofertilizer EM1 increased total soluble solids (TSS) and total sugar contents while producing the lowest nitrate (NO3) percentage in ‘Murcott’ mandarin fruit compared with trees fertilized with inorganic nitrogen only. The fruit produced by ‘Murcott’ mandarin trees fertilized with 100% of RD as organic nitrogen with or without biofertilizer EM1 contained higher TSS, total carbohydrates, and sugars and lower nitrate percentages than those fertilized with inorganic nitrogen and biofertilizer EM1. This study contributes to reducing the use of inorganic fertilizers by adding a percentage of an organic fertilizer to obtain a healthy product that contains a lower percentage of NO3, which affects the health of the consumer, and is of high quality and suitable for export.